Efektivitas Penggunaan Teknologi Informasi Di Madrasah Ibtidaiyah Negeri 2 Kota Palembang - Sastrawati, Ratna; Asteriniah, Femi; Mahriadi, Nopriawan (@-Publik: Jurnal Administrasi Publik, 2025)
One of the schools that incorporates technology into the teaching and learning process is Madrasah Ibtidaiyah Negeri 2 in Palembang City. Madrasah Ibtidaiyah Negeri 2 Palembang City's information technology program has resources that are available for effective use and can offer fresh ideas that can be applied to each lesson, like computer/laptop assisted learning and internet-based learning. This study set out to evaluate the efficiency of information technology use at Madrasah Ibtidaiyah Negeri 2 in Palembang City. The issue in this study is that school operators still don't fully understand the Educator and Education Staff Information System (SIMPATIKA) and the Emis Applications. Signals or applications frequently experience overload because many operators have access, and the necessary human resources, specifically only 1 school operator, are still lacking. A qualitative data analysis technique was employed in this study. This study demonstrates that Palembang City 2 Elementary School has successfully used information technology overall. Signals or applications frequently experience overload because many operators have access and the necessary human resources are still lacking, namely only 1 operator school, despite the fact that there are still obstacles in its implementation, such as the lack of understanding of school operators about Emis Applications and the Information System for Educators and Education Personnel (SIMPATIKA).